Prospect of biodiesel production from waste oil and fat in Malaysia - Su, M.C.H (Universiti Malaysia Sarawak, UNIMAS, 2010)
Biodiesel is one of the alternative fuels which are derived from straight or used vegetable oils and animal fats. It is a biodegradable, renewable energy and clean burning alternative. This paper presents a comparative study on efficiency of conversion of waste oil and fat to biodiesel and the performance of diesel engine using waste oil and fat biodiesel. The base-catalyzed transesterification method was used to produce biodiesel from waste oils (waste palm oil, waste coconut oil and waste sunflower oil) and fats (beef tallow, duck tallow and chicken fat). The conversion of waste coconut oil (97%) and duck tallow (96.4%) to biodiesel produced the highest yield. However, the conversion of waste palm oil (91%) and chicken fat (94%) to biodiesel resulted in lowest yield. Short-term engine performance tests were carried out on test diesel engine fuelled with waste oil or fat biodiesel blends from B0 to B50. It was found that waste oil and fat biodiesel blends showed a decrease in engine power output, brake horse power and mechanical efficiency. Conversely, the specific fuel consumption increased with blending percentage. While fueling diesel engine with waste coconut or beef oil biodiesel, it resulted in lowest drop in engine power output and mechanical efficiency. Overall, B20 biodiesel blend for all waste oils and fats resulted lower variation in engine performance when fueling in diesel engine. It is recommended a further research should be taken to improve the brake horse power, power output and reduction in the specific fuel consumption.